If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (3x + -5) * -2 = -8 Reorder the terms: (-5 + 3x) * -2 = -8 Reorder the terms for easier multiplication: -2(-5 + 3x) = -8 (-5 * -2 + 3x * -2) = -8 (10 + -6x) = -8 Solving 10 + -6x = -8 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + -6x = -8 + -10 Combine like terms: 10 + -10 = 0 0 + -6x = -8 + -10 -6x = -8 + -10 Combine like terms: -8 + -10 = -18 -6x = -18 Divide each side by '-6'. x = 3 Simplifying x = 3
| 53+5=x | | -10=-p-p | | x/x-1=8/x+2 | | x-64=389 | | 5-2r=3+7-3r+3 | | x+3=5-3 | | H(t)=-16t+32t+5 | | 5+n/20=6 | | .05x+.25x+.5x=24 | | 5=4x-5x | | 9+(-1)=16 | | 9x+20x= | | v=4/3x3.14x8 | | -9=1+5n+5 | | -9-6v=69 | | 6x+2=2+x+5x | | x-16=-26 | | 8-2x/3+2x+4/9+12 | | 15-13= | | 4-x=17 | | 2n-9=-17 | | 9+x=33 | | 5m+m=0 | | x^2-2/12+x/6 | | 5/4(2c-1)=3c-2 | | 14=6+3x-5x | | 100+1000= | | -3/4t-8=-8 | | 6y^2+42=0 | | 14+-1y=y+2 | | 72=9r | | 3x^2-44x+10000=0 |